The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.4049/jimmunol.179.9.5686
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Role of Neutrophil Lactoferrin in RelA/p65 Phosphorylation on Ser536 by Recruiting TNF Receptor-Associated Factors to IκB Kinase Signaling Complex

Abstract: The activation of NF-κB by neutrophil lactoferrin (Lf) is regulated via the IκB kinase (IKK) signaling cascade, resulting in the sequential phosphorylation and degradation of IκB. In this study, we observed that Lf protein augmented p65 phosphorylation at the Ser536, but not the Ser276 residue, and stimulated the translocation of p65 into the nucleus. Lf was also shown to enhance the association between p65 and CREB-binding protein/p300 in vivo. To elucidate the mechanism by which Lf triggers these signaling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
1
11
1
Order By: Relevance
“…The transcription factor NF-kB is known to play a central role on the regulation of inflammatory and immune responses and on the control of cell mitosis and apoptosis (45). In opposition to the studies of Conish et al (8), Oh et al (35) reported in neutrophils an activation of NF-B by LF concentration ranging from 20 to 100 g/ml. This suggests that LF can trigger different pathways, depending on the target cells.…”
Section: Discussionmentioning
confidence: 95%
“…The transcription factor NF-kB is known to play a central role on the regulation of inflammatory and immune responses and on the control of cell mitosis and apoptosis (45). In opposition to the studies of Conish et al (8), Oh et al (35) reported in neutrophils an activation of NF-B by LF concentration ranging from 20 to 100 g/ml. This suggests that LF can trigger different pathways, depending on the target cells.…”
Section: Discussionmentioning
confidence: 95%
“…This phosphorylation event occurs after NF-κB dissociation from its cytoplasmic inhibitor IκB and serves to slow down its export from the nucleus back to the cytosol, thus increasing the amplitude of NF-κB-induced gene transactivation. Ser536 phosphorylation also promotes NF-κB mediated transcription via recruitment of other transcription coactivators such as p300, enlarging the scope of proinflammatory activities [60]. LPG and CPI-GC also induced phosphorylation of ERK1/2, which is activated in macrophages upon trichomonad infection and linked to host cell apoptosis [61].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to enhanced acetylation of K310, we also show that DC-SCRIPT knockdown leads to enhanced phosphorylation of Ser 536 NFkBp65. Interestingly, it has been shown that enhanced phosphorylation of this specific site is linked to enhanced interaction between NF-kBp65 and p300/CBP (54). Therefore, it is tempting to FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%